Psychology of Mental Health: Non Followers to Spirituality - bhambri, Shivani; Mahapatra, Mamata (International Journal of Psychosocial Rehabilitation, 2020)
As we all know that Spirituality has a positive effect on physical as well as on mental health. In the era of globalization stress is a part of life. Spirituality is linked to better health, less hypertension, less stress during difficult times, more positive feelings, less depression, greater psychological well being, and superior ability to handle stress. Many Mental Health experts believe that spirituality is important in ones lives. But there are people who do not follow spirituality at all. Spirituality helps us in maintaining inner peace which people are lacking in, Inspite of having everything people are not happy and when you yourself are not happy you tend to remain alone, does not want to mingle, does not want to talk to anyone. Thus, individual behavior varies. Followers of spirituality are more happy and contented hence is more resilient. They have more faith and maintain good relations with everyone. In this IT dominated world there are crimes which are getting worse day by day. Spirituality is the solution to all of these problems. People who do not follow spirituality don’t keep good relations with people around them and they are less happy and less contented as compared to followers of spirituality. Align to the above understanding the researchers have taken a sincere attempt to study the psychology of people in the society who are not following spirituality in their life. Present researchemphasized on the importance of Spirituality and mental health. In the present paper the researchers have attempted in depth analysis of non followers to spirituality. The sample of the study consists of 400 non followers to spirituality. Sample was collected in two of the States i.e. Delhi and Rajasthan. The results revealed that there is relationship between mental health and spirituality of non followers to spirituality. Mental health was determined with the help of Mental Health Inventory developed by Dr Jagdish and Dr Srivastav. Spirituality was determined with the help of spirituality assessment scale developed by Judy.W.Howden. Research indicates that there are people who do not follow spirituality at all and there are people who pretend to show that they follow spirituality but their behavior indicates that we can consider them under the category of non followers.